2017
DOI: 10.1111/jphp.12842
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of triiodothyronine on the chondrogenic differentiation of mesenchymal stem cells from the bone marrow of female rats

Abstract: Objectives Verify the in-vitro effect of triiodothyronine (T3) on the chondrogenic differentiation of female rat bone marrow mesenchymal stem cells (BMMSCs) over several time periods and at several doses. Methods CD54 + /CD73 + /CD90 + BMMSCs from Wistar female rats were cultured in chondrogenic medium with or without T3 (0.01; 1; 100; 1000 nM). At seven, 14 and 21 days, the cell morphology, chondrogenic matrix formation and expression of Sox9 and collagen II were evaluated. Key findings The dose of 100 nM did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Before the BMSCs of this study were subjected to chondrogenic differentiation, cell viability was evaluated to ensure the continuity of the experiment and the differentiation process as performed by other previous studies (Alves et al, 2016;Assis et al, 2018). In this regard, both studied groups showed viability greater than 90% without a significant difference between these groups.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Before the BMSCs of this study were subjected to chondrogenic differentiation, cell viability was evaluated to ensure the continuity of the experiment and the differentiation process as performed by other previous studies (Alves et al, 2016;Assis et al, 2018). In this regard, both studied groups showed viability greater than 90% without a significant difference between these groups.…”
Section: Discussionmentioning
confidence: 94%
“…Cell morphology was assessed after 14 and 21 days of differentiation. Samples were washed with 0.15 M PBS and fixed in 10% buffered formaldehyde for one hour, processed by the routine paraffin embedding method (Assis et al, 2018;Solchaga et al, 2011). Subsequently, the samples were subjected to microtomy to obtain 4 µm thick sections and stained with Hematoxylin and Eosin for morphology analysis and stained with Periodic Schiff Acid (PAS) for the analysis of chondrogenic matrix formation.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of 21 days of culture, the chondrocyte pellets of all groups under 3D culture in 15 mL conical tubes were washed with 0.15 M PBS and fixed with 4% paraformaldehyde. The pellets were then processed into paraffin blocks 22 and subsequently sectioned into 5-μm slices using a microtome. The histological sections were placed under gelatinized glass slides 23 and stained by the periodic acid Schiff (PAS) (Sigma-Aldrich, St. Louis, MO, USA) to determine the percentage of PAS+ cartilaginous matrix.…”
Section: Methodsmentioning
confidence: 99%
“…The role of thyroid hormones in stem cell function is still unclear and further study is required. Previous investigations have shown that the thyroid hormone T 3 exerts a dose-dependent effect on the chondrogenic and osteogenic differentiation of BMSC in female rats, promoting chondrogenic matrix formation and collagen synthesis respectively [22, 23]. T 3 treatment increases the differentiation of BMSCs induced to cardiomyocytes and promotes their maturation [24].…”
Section: Introductionmentioning
confidence: 99%